Vetch as a new protein source for the human diet - Riley, Samuel (2023)
Common vetch (Vicia sativa) is a leguminous plant currently used as an intermediate cover crop, protecting the fragile topsoil from erosion whilst providing a natural source of soil nitrogen. Due to characteristically high drought tolerances and yields, vetch has the potential to become both a cheap and accessible protein source in many parts of the world, acting as feed for both livestock and humans. Agricultural uptake has been limited due to anti-nutritional compounds, β-cyano-L-alanine (BCA) and primarily the dipeptide γ-glutamyl-β-cyano-L-alanine (GBCA), in the seeds which are highly toxic to monogastric animals. However, the molecular mechanisms underlying this neurotoxicity are largely unknown. To further understand BCA and GBCA neurotoxicity mechanisms, establishment of a neurotoxicity assay using differentiated SH-SY5Y cells was established. Further proteomics analyses found that BCA deregulates cellular proteins involved in DNA damage whilst GBCA dysregulates proteins involved in mitosis and cell cycle. These mechanisms will be useful in informing the criteria of future animal trials aiming to test potentially zero-toxin samples of V. sativa. In efforts to reduce concentrations of these undesirable two compounds, the novel post - harvest processing method of Bacillus subtilis var. natto bacterial fermentation was successfully applied to both whole and de-hulled V. sativa seeds and lowered GBCA abundance to analytically undetectable levels. This processing step shows great promise for incorporation of fermented V. sativa into animal feed. To assess suitability of V. sativa as a future source of dietary protein, volatile aroma profiles and the mechanisms behind vetch flavour development following processing were investigated by SPME GC-MS. Characteristic volatiles of vetch were described for the first time being: 2-pentyl furan, benzyl alcohol, benzaldehyde, 1-octen-3-ol and 1-hexanol. Significant intraspecies variation in volatile abundance between wild and commercial cultivars was observed. Processing by Rhizopus oligosporus fermentation to produce tempeh was found to significantly lower concentrations of off flavour 1-octen-3-ol, indicating the potential of post-harvest processing to create favourable aroma profiles in future commercial V. sativa.